1997
DOI: 10.1002/1521-396x(199701)159:1<243::aid-pssa243>3.0.co;2-5
|View full text |Cite
|
Sign up to set email alerts
|

Time Resolved Investigation of the Hydrogen Evolution Reaction on Ag(111), Ag(100), Smooth Polycrystalline, and Activated Polycrystalline Silver Surfaces

Abstract: Experiments on the hydrogen evolution by hot electrons at activated silver top electrodes of metal/insulator/metal (MIM) junctions demonstrated the existence of a transient adsorbed hydrogen species at the silver electrolyte interface. In the present work we investigated the hydrogen evolution on Ag(111), Ag(100), smooth polycrystalline, and activated silver surfaces in neutral and acid electrolytes with the help of cyclovoltammograms and potentiostatic current transients after cathodic potential pulses. In ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 21 publications
1
20
0
Order By: Relevance
“…17,218 Diesing et al found that the hydrogen evolution reaction is promoted when a bias voltage is applied to the metal−insulator−metal junction. 72 The promotion of decomposition of chlorinated hydrocarbons by electron emission was observed by Sharpe et al 83 Bias voltage-induced decomposition of 2-methyl-1,4-naphthoquinone was observed by Wadayama et al on the MIM tunnel junction. 84 Wadayama et al used surface-enhanced Raman spectroscopy (SERS) to uncover the hot electron-induced surface reaction of p-nitrobenzoic acid (PNBA) adsorbed on a Ag top electrode in a Ag/AlO x /Al tunnel junction.…”
Section: Influence Of Hot Electrons On Atomic and Molecular Processesmentioning
confidence: 94%
“…17,218 Diesing et al found that the hydrogen evolution reaction is promoted when a bias voltage is applied to the metal−insulator−metal junction. 72 The promotion of decomposition of chlorinated hydrocarbons by electron emission was observed by Sharpe et al 83 Bias voltage-induced decomposition of 2-methyl-1,4-naphthoquinone was observed by Wadayama et al on the MIM tunnel junction. 84 Wadayama et al used surface-enhanced Raman spectroscopy (SERS) to uncover the hot electron-induced surface reaction of p-nitrobenzoic acid (PNBA) adsorbed on a Ag top electrode in a Ag/AlO x /Al tunnel junction.…”
Section: Influence Of Hot Electrons On Atomic and Molecular Processesmentioning
confidence: 94%
“…This clearly increased both when the pH of the blank solution was decreased and when solution was stirred. Then, the second reduction process detected during silver electrodeposition (peak II) was assigned to proton reduction [15].…”
Section: Silver Deposition From Free-thiourea Bathmentioning
confidence: 67%
“…The hydrogen evolution reaction on silver electrodes follows the Volmer-Heyrowski mechanism, in which H ads is formed as reaction intermediate, a prewave appearing in perchlorate medium corresponding then to H ads formation [15]. From our voltammetric results, we can deduce that 9.…”
Section: Discussionmentioning
confidence: 99%
“…The study of the onset potential of her as a function of pH on Ag(hkl) was first reported by Diesing et al by means of surface resistance measurements [19]. They have found that the two faces have the same onset potential of her in 0.1 M HClO 4 , but differ in neutral solution.…”
Section: Cyclic Voltammetry and R(φ) Plotsmentioning
confidence: 96%